(untitled) (Archives of Clinical Psychiatry, 2009)
BACKGROUND: Drug use among adolescents has been investigated in several recent studies. Family is recognizably both a protective and a risk factor for substance use during adolescence. OBJECTIVE:This present article is a literature review on family aspects of female adolescents who are drug abusers and/or psychoactive drug dependents to gather information available on this issue for capacitating heath providers in clinical care and prevention of this syndrome. METHODS:A literature review was conducted in MedLine (Index Medicus), SciELO, PubMed using the following key words: addiction, drug abuse, girls, adolescence and family. RESULTS:The families of these adolescents were found to be mostly dysfunctional characterized by conflictive family relationships, poor family cohesion, ill-defined hierarchy, and negative parental role modeling for drug use. Gender differences were also remarkable: girls need more family support than boys to protect them against deviant peer group involvement; they are also more vulnerable to psychological rather than physical abuse while boys suffer more from physical abuse. Notably, support from older female siblings is a protective factor against substance abuse in girls. Transgenerational transmission and parental style are also addressed. DISCUSSION: Drug abuse in girls has been little investigated and there have been few studies specifically focusing on the association between dependence and girls.